2022
DOI: 10.15605/jafes.037.01.03
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Protocol for Critical Illness-Related Corticosteroid Insufficiency (CIRCI) at a Tertiary Hospital

Abstract: Objectives The diagnosis and management of critical illness-related corticosteroid insufficiency (CIRCI) remains a challenge. This initiative aimed to develop a protocol for the diagnosis and management of CIRCI which will facilitate informed decision-making among clinicians through consensus-building among a multi-disciplinary team. Methodology This was a single-center, qualitative study which utilized the modified Delphi method, consisting of a sequential iterative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…27 In this cohort of COVID-19-positive patients, the median cortisol level was at 25.26 mcg/dl compared to 24.15 mcg/dl for the non-COVID subgroup in the same institution. 28 However, a notable factor that ought to be considered is that not all patients in this cohort had random serum cortisol results because, in most of the patients, CIRCI was diagnosed based on the presence of refractory shock and subsequent therapeutic response to corticosteroids. The small sample size of patients with cortisol results could have served as a barrier in detecting significantly low cortisol levels in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…27 In this cohort of COVID-19-positive patients, the median cortisol level was at 25.26 mcg/dl compared to 24.15 mcg/dl for the non-COVID subgroup in the same institution. 28 However, a notable factor that ought to be considered is that not all patients in this cohort had random serum cortisol results because, in most of the patients, CIRCI was diagnosed based on the presence of refractory shock and subsequent therapeutic response to corticosteroids. The small sample size of patients with cortisol results could have served as a barrier in detecting significantly low cortisol levels in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the question about the duration of steroid supplementation is still debated. A recent work, by Arcellana et al [ 37 ] indicated that 200 mg/day hydrocortisone should be given for at least 72 h and up to 7 days, to have a significant benefit [ 1 , 38 ], but no univocal indication is provided about this topic.…”
Section: Managementmentioning
confidence: 99%
“…CIRCI describes the impairment of HPA axis during critical illness, and in most of the cases, it is associated with dysregulation of the HPA axis, tissue corticosteroid resistance, and altered cortisol metabolism. In clinical practice, refractory shock unresponsive to fluid resuscitation and vasopressors might suggest the presence of CIRCI, and it has been suggested that patients with probable CIRCI should immediately be treated with glucocorticoids [ 30 ]. Moreover, current evidence indicates that there are also some changes resulting in mineralocorticoid dysfunction during critical illness, and hyperreninemic hypoaldosteronism has been demonstrated.…”
Section: Pathophysiologymentioning
confidence: 99%